An Analysis of Transitivity of the Main Character “Barbie” in the Barbie Movie - Selfiyani Ketaren; Tiara Kristina Pasaribu; Jubil Ezer Sihite (Journal of Language Education (JoLE), 2025)
This study aims to find out the types of processes that occur and the realization of the transitivity system in Barbie films. With the transitivity system, the writer can find out the characters and messages conveyed in the film through the main character describing her thoughts and feelings. This thesis uses the theory of Systemic Functional Grammar by M. A. K Halliday by using descriptive qualitative method. The data in this study is from the Barbie movie script, which focuses only on the utterances of the main character, Barbie. The results of the analysis showed that in this movie there were all types of transitivity (6 types) processes. The types of transitivity consist of the relational process (140 data) with percentage 44%, material process (79 data) with percentage 25%, mental process (63 data) with percentage 20%, behavioral process (22 data) with percentage 7%, verbal process (11 data) with percentage 3%, and existential process (2 data) with percentage 1%. The relational process is the most common process in this study. Carrier and attribute are the most common participants that appeared in clauses. For circumstance, location is the most common circumstance in clauses, both temporal and spatial location. The relational process indicates that through the role of Barbie, it can be seen this movie provides a detailed explanation of the relationship between one and the other like Barbie's relationship with Ken and also with her creator, Ruth Handler. The movie’s script has a good structure because the type of participant and the process have a balance of occurrence in the clause.